Analysis of hydrogen embrittlement in palladium–copper alloys membrane from first principal method using density functional theory. (November 2022) - Opetubo, Oriyomi; Ibitoye, Ayotunde Idris; Oyinbo, Sunday Temitope; Jen, Tien-Chien
Abstract: Hydrogen embrittlement has significant effects on membrane properties, and it is vital to develop countermeasures to avoid this problem from the start. The impact of hydrogen on pure palladium and palladium-copper alloys used for hydrogen purification/separation was investigated in this study. It was discovered that the lattice parameter and crystalline structure of pure Pd change from 3.92 Å to 5.55 Å and from cubic structure to triclinic structure, respectively. The presence of hydrogen atoms in the crystalline structure is responsible for this alteration. The absorption enthalpy of Pure Pd and PdCu of −4.38eV and −4.86eV, respectively, showed that a PdCu membrane with a lower enthalpy value increased anti-hydrogen brittleness. Due to hydrogen exposure, the mechanical characteristics of pure palladium were considerably affected. This study demonstrates that the mean peak on EF of Pd–Cu (0.259eV) is lower than that of pure Pd (0.955eV) when exposed to hydrogen, indicating more stability and lower hydrogen embrittlement in Pd–Cu alloy than pure Pd. Density functional theory-based simulation is used to analyse what happened at the grain boundary, the causes of hydrogen embrittlement, and possible ways to prevent it. Highlights: Using density functional theory (DFT) to model hydrogen adsorption/absorption on the Pd and PdCu alloy. Pure Pd with a higher enthalpy value is more stable, but PdCu with a lower value supports anti-hydrogen embrittlement. Pure Pd and Pd–Cu are more stable than Pd–H and PdCu–H compounds. Hydrogen embrittlement rate can be mitigated by alloying pure Pd used for hydrogen-absorbing applications.